Elevated baseline plasma phospholipid protein (PLTP) levels are an independent predictor of long-term all-cause mortality in patients with diabetes mellitus and known or suspected coronary artery disease. Issue 2 (April 2015) - Cavusoglu, Erdal; Marmur, Jonathan D.; Chhabra, Sandeep; Hojjati, Mohammad R.; Yanamadala, Sunitha; Chopra, Vineet; Eng, Calvin; Jiang, Xian-Cheng
Abstract: Objectives: To investigate the long-term prognostic significance of baseline plasma PLTP levels in a group of well-characterized male patients with diabetes mellitus and known or suspected coronary artery disease referred for coronary angiography. Background: PLTP is a plasma protein that mediates the net transfer and exchange of phospholipids between lipoproteins. It has been implicated in the pathogenesis of atherosclerosis and elevated plasma levels have been reported in patients with diabetes mellitus. Methods: Baseline plasma PLTP levels were measured in 154 male patients with diabetes mellitus who were referred for coronary angiography and followed prospectively for 5 years for the development of all-cause mortality. Results: After adjustment for a variety of baseline clinical, angiographic and laboratory parameters, plasma PLTP levels (analyzed as a continuous variable) were an independent predictor of all-cause mortality at 5 years (HR, 1.55; 95% CI, 1.22–2.00; P = 0.0009). Furthermore, in 3 additional multivariate models that also included a wide variety of contemporary biomarkers with established prognostic efficacy (i.e., ST2, GDF-15, Cystatin C, Fibrinogen, and NT-proBNP), PLTP remained an independent predictor of all-cause mortality at 5 years. Conclusions: Elevated baseline plasma levels of PLTP are associated with an increased risk of long-term all-cause mortality in patients with diabetes and known or suspected coronary disease. Furthermore, this association is independent of a variety of clinical, angiographic, and laboratory variables, including a whole host of contemporary biomarkers with established prognostic efficacy. Highlights: PLTP is a plasma protein that mediates the net transfer and exchange of phospholipids between lipoproteins. PLTP has been implicated in the pathogenesis of atherosclerosis. Elevated plasma PLTP levels have been reported in patients with diabetes mellitus. Elevated plasma PLTP levels are an independent predictor of mortality in diabetic patients undergoing coronary angiography.